2019
DOI: 10.1155/2019/9278270
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Acupuncture during LTP-Like Plasticity Induced by Paired-Associative Stimulation

Abstract: The aim of this study was to investigate the time-dependent effects of acupuncture on the excitability and long-term potentiation- (LTP-) like plasticity induced by paired-associative stimulation (PAS) over the primary motor cortex (M1). The present examination is the first to report the influence of acupuncture on the motor-evoked potential (MEP) throughout the treatment process, including baseline (before acupuncture), the needle in situ, and the needle removal. Subsequently, the LTP-like plasticity induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
12
0
3
Order By: Relevance
“…Our previous study demonstrated that the MEP amplitude after simple acupuncture-in gradually decreased and slowly recovered in the shape of a “V,” immediately rose, and then continued to slowly rise after extraction of the needle. Both simple acupuncture processes did not exceed 20 min, which may be a short-term inhibition or potentiation, in accordance with the results of simple acupuncture examinations of the modulatory effect on cortical plasticity ( Chen et al, 2006 ; He et al, 2019 ). Researchers have suggested that simple acupuncture needling or LFS ( Huang et al, 2001 ) that affects cortical excitability may be related to the plasticity processes mediated by N -methyl- D -aspartic (NMDA) receptors.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our previous study demonstrated that the MEP amplitude after simple acupuncture-in gradually decreased and slowly recovered in the shape of a “V,” immediately rose, and then continued to slowly rise after extraction of the needle. Both simple acupuncture processes did not exceed 20 min, which may be a short-term inhibition or potentiation, in accordance with the results of simple acupuncture examinations of the modulatory effect on cortical plasticity ( Chen et al, 2006 ; He et al, 2019 ). Researchers have suggested that simple acupuncture needling or LFS ( Huang et al, 2001 ) that affects cortical excitability may be related to the plasticity processes mediated by N -methyl- D -aspartic (NMDA) receptors.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the literature and it is believed that LTP-like plasticity is produced over the stimulus cortical side. Preclinical and clinical studies have confirmed that the induction of LTP is related to the intensity and time-dependent on stimuli ( Fino et al, 2010 ; Zhang et al, 2010 ), regulates the magnitude and direction of MEP induction ( He et al, 2019 ), and is involved in two mechanisms of homeostatic plasticity or gating mechanisms ( Karabanov et al, 2015 ; Yee et al, 2017 ). Recently, several studies have reported that homeostatic plasticity plays an important role in the control of synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the brain area acupuncture research is concerned with the hippocampus and cortex [ 50 53 ]. For example, in the previous study, it was found that acupuncture modulated the excitability of the motor cortex, and the plasticity was time-dependent [ 54 ]. Furthermore, it was suggested that the synaptic effect may be due to the changes in the synaptic structure of the brain, the detection time, and the acupoint [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in this study are similar to those reported in previous studies. One study found that after the removal of the needle on LI11 and TE5 (both located on the forearm), the MEP amplitude of FDI was significantly increased compared to baseline [ 37 ]. Moreover, peripheral nerve stimulation at the wrist was shown to simultaneously induce marked changes in the cortical excitability of multiple hand muscles [ 5 ].…”
Section: Resultsmentioning
confidence: 99%